RAGBY-HISTORICKO SPOLEČENSKÝ VÝVOJ HRY U NÁS A V ZAHRANIČÍ [RUGBY- SOCIO HISTORICAL DESCRIPTION OF THE GAME ABROAD AND IN THE CZECH REPUBLIC] - Šárka Vašíčková (Palacký University Olomouc, 2009)
Příspěvek seznamuje čtenáře s historií, společenským vývojem a současnou situací ve sportu ragby. Věnuje se hlavně zemím, kde byl, je a pravděpodobně bude tento sport jeden z nejpopulárnějších. Jednotlivé země jsou porovnány z hlediska historického a sociálního vývoje. Sport je ukázán jako společenský činitel a jakýsi zpětný obraz celkového vývoje v uvedených zemích. V první části je popsán vznik hry a základní pravidla. V druhé části je popsán sport, jako společenský hybatel v jednotlivých zemích. V poslední části je charakterizován vývoj hry v České republice, zaměřeno hlavně na historii a specifické prvky českého ragby. Závěr potom hodnotí tento sport na současné sportovní scéně a jeho popularitu u nás a ve světě. [The paper familiarizes readers with the socio-historical movements in the game rugby. Particularly, in the first part, it's social background in the country of origin-England, historical comparison of different games, social influence of the game in the different regions of England. Secondly, as the consequence of my papers, I focused on the country of the Commonwealth of Nations-the Republic of South Africa. As a result of social changes, that influenced not only political orientation of the country but also relation of social groups to sport and particularly rugby played it's specific role. On one hand it was the symbol of English social group, sport only for "white" people. On the other hand it became the occasion, where the nation of rainbow united after 1992. In the last parted I focus on the Czech Republic and rugby history. However this game typical for Anglo-Saxon countries is it became popular after the First World War. Different social structure in the Czech Republic gave to this game it's specific character. I pay attention to this national characteristic and try to show the development of the game in the middle European country.]